Fairy tale : a novel - King, Stephen, 1947- (New York ; Scribner, 2022)
Charlie Reade, he carries a heavy load. His mom was killed when he was ten, and grief drove his dad to drink. Charlie learned how to take care of himself$1 (Band his dad. When Charlie is seventeen, he meets a dog named Radar and her aging master, Howard Bowditch, a recluse in a big house at the top of a big hill. Charlie starts doing jobs for Mr. Bowditch and loses his heart to Radar. Then, when Bowditch dies, he leaves a cassette tape for Charlie, telling him the secret he has kept secret all his long life and it is unbelievable!s
Keywords: Teenagers -- Fiction; Good and evil -- Fiction; Human-animal relationships -- Fiction; Older people -- Fiction; Doorways -- Fiction; Thrillers (Fiction); Fantasy fiction; Science fiction; Horror fiction